ANALYSIS OF LANDSLIDE DISASTER POTENTIAL IN MEULABOH AREA, WEST ACEH REGENCY, ACEH USING RESISTIVITY AND GEOSPATIAL METHODS - Agnia, Lasin; Amsir, Amsir; Marwan, Marwan; Masrurah, Zakia; Pramana, Agus Hari (Indonesian Physical Review, 2025)
Meulaboh, in West Aceh Regency, is one of the areas with potential for landslides. The goal of this research is to identify soil conditions that could lead to landslides based on resistivity data, as well as to analyze the distribution of landslide potential using geospatial data. This research provides benefits to various stakeholders, including the government. It contributes to improved disaster mitigation planning, reduced risk of losses, and the selection of appropriate materials to construct more disaster-resilient infrastructure. The research methods used are 2D resistivity and geospatial methods with weighted overlay analysis. Based on the processing results of 2D resistivity data from profiles 1 and 2, the study area is characterized by silt, sand, and sandstone. The resistivity values of the material in profile 1, identified for silt, range between 1 and 119 Ω.m at depths of 2-59 meters. For sand, the resistivity values range between 120-225 Ω.m at 2-61 meters depths. Sandstone has resistivity values that range between 226-500 Ω.m at depths of 3-62 meters. The resistivity values of the material in profile 2, identified for silt, range between 1-119 Ω.m at depths of 1.5-60 meters. For sand, the resistivity values range between 120-225 Ω.m at 9-59 meters depths. Sandstone has resistivity values that range between 226-500 Ω.m at depths of 15-39.4 meters. The presence of silt (1-119 Ω.m) increases the potential for landslides due to its cohesive nature. Based on the weighted overlay analysis processing results, the study area has a moderate potential for landslides. The study area has characteristics such as a gentle to steep slope (8-45%), a high rainfall rate (2500-3000 mm/yr), a lithology consisting of rocks from the Tutut Formation, including silt, sand, and a small amount of conglomerate, and land that is used for plantations and rice fields.